IMMU-22. THE IMPACT OF MICROGLIA MODULATION ON GBM PROGRESSION IN SYNGENEIC MOUSE MODELS. (12th November 2021) - Ritz, Marie-Françoise; Shekarian, Tala; Martins, Tomás A; Schmassmann, Philip; Hutter, Gregor
Abstract: BACKGROUND: The tumor immune microenvironment (TME) of Glioblastoma consists of almost myeloid-derived macrophages and microglia called TAMs. We have shown that the disruption of CD47-Sirpα-axis induces an antitumor activity of TAMs against GBM in immune-deficient mice, through increases of phagocytosis of tumor cells by TAMs. We have aimed to study the role of microglia and its activation/depletion on GBM progression, in the syngeneic GBM model in immune-competent mice. We have studied the interplay of innate and adaptive immune response after activation and depletion of microglia and the effect on tumor progression and outcome of the mice. MATERIAL AND METHODS: We used different colonies of genetically modified immunocompetent mouse strains to genetically activate/deplete microglia in the tumor context. We generated Sall1 CreERT2/fl mice and Cre-negative littermates. The application of Tamoxifen in this constellation leads to the excision of the transcription factor Sall1 and subsequent enhanced microglia activity. Conversely, we generated Sall1 CreERT2 x Csf1r fl/fl animals and the respective heterozygous and Cre-negative littermates in which Tamoxifen treatment leads to inactivation of microglia through the deletion of Csf1r. Glioblastoma tumors were induced by intracerebral injection of GL261, CT2A, or retrovirus-induced PDGF-Akt in pups and Tamoxifen treatment was started once the tumors were detected. RESULTS: We observed a survival advantage in tumor-bearing mice after activation of microglia in Sall1 CreERT/fl animals compared to Cre-negative littermates. Genetic depletion of microglia in this model resulted in a shorter lifespan in microglia-depleted animals compared to Cre-negative littermates. Furthermore, the iTME in these tumors is subjected to scRNAseq analysis to identify mechanistic insights. CONCLUSION: Microglia are important players in tumor development and progression of glioblastoma in mouse models. These cells may be targeted in future immunotherapeutic approaches for patients.